Crossways : drawings and works on paper by eighteen american and european painters - Bungert, Petra (New York : [s.n.], 1994)
Brandl, Herbert ; De Keyser, Raoul ; Förg, Gunther ; Fosdick, Robert ; Frecon, Suzan ; Heilmann, Mary ; Huber, Ika ; Jeffrey, David ; Jenssen, Olav Christopher ; Korman, Harriet ; Metzner, Helmut ; Mosset, Olivier ; Tilman ; Uglow, Alan ; Usle, Juan ; Vedova, Emilio ; Waltemath, Joan ; Zimmermann, August
Uitgegeven in eigen beheer. Crossways : drawings and works on paper by eighteen american and european painters. Traveling group exhibition. Crossways is scheduled to open in spring of 1996 in New York City. the touring time will be approximately one year.
boek